Ab initio study on electronic structure and magnetic properties of AlN and BP monolayers with Ti doping. (October 2021) - Wang, Min; Li, Hui; Ren, Jie; Gao, Leyuan; Feng, Tianlong; Hao, Zhi; Yue, Yunliang; Zhou, Tiege; Hou, Denglu
Abstract: The spintronic properties of Aluminum Nitride (AlN) and Boron Phosphide (BP) monolayers with Titanium (Ti) doping have been studied by using first principles calculation. The Ti-doped AlN monolayer will produce the magnetic moment of 1 μ B, which is mainly contributed by d orbital of the impurity. Although TiP (Phosphorus was replaced by Ti) can lead to semi-metallic properties in BP monolayer, TiB (Boron was replaced by Ti) has a lower formation energy. The magnetic moment produced by TiB is 1 μ B, which is also mainly contributed by the Ti- d orbital. The strain studies show that the band gap of AlN monolayer will decrease with the increase of strain, while the pristine BP monolayer increases. TiB will make the band gap of BP increase first and then decrease when it is 10%. Studies on magnetic coupling indicate that ferromagnetic and antiferromagnetic coupling oscillations will occur at different Ti-Ti distances in the AlN monolayer. However, TiB -TiB are always coupled antiferromagnetically at each distance in the BP monolayer. Further study shows that the Néel temperature of the BP system with TiB may be higher than room temperature. Graphical abstract: Image 1 Highlights: Applying strain can regulate the band gap of AlN and BP materials regularly. The magnetic coupling between Ti atoms in AlN monolayer will oscillate regularly. The results show that TiP will make BP monolayer produce semi-metallic properties. The study found that TiB -doped BP has a Néel temperature above room temperature.